Physical Therapy Reduces Bone Resorption and Increases Bone Formation in Preterm Infants - Vignochi, Carine Moraes; Silveira, Rita C.; Miura, Ernani; Canani, Luis Henrique Santos; Procianoy, Renato S. (American Journal of Perinatology, 2012)
Aim To evaluate bone metabolism in newborn preterm infants before and after a physical therapy protocol.Method This randomized controlled clinical trial included 30 newborn preterm infants with gestational age ≤35 weeks and appropriate weight for gestational age, who were randomized into control group (CG) and physiotherapy group (PG). The PG protocol consisted of 15 minutes of daily passive movements with gentle joint compression 5 days a week. Daily data were obtained on feeding and body weight. Measurements of bone-specific alkaline phosphatase (BAP) and urinary deoxypyridinoline (DPD) were collected before and after intervention in both groups. The analysis of covariance test was performed to compare the means of both groups.Results At baseline, gestational age and corrected gestational age, birth weight, and gender were similar between both groups. Nutrient supply, length of total parenteral nutrition, and mechanical ventilation were also similar. BAP level increase in PG was 22.44 ± 3.49 U/L, whereas in CG was 2.87 ± 3.99 U/L (p = 0.003). There was a reduction of DPD levels in PG of 28.21 ± 11.05 nmol/mmol, and an increase of 49.95 ± 11.05 nmol/mmol (p < 0.001) in GC.Conclusion The benefits of prevention and treatment of metabolic bone disease of prematurity, in addition to an adequate diet, should include these passive exercises with gentle joint compressions to improve the quality of premature infant's bones.
Keywords: preterm; bone; physiotherapy; osteopenia